Phytase production by solid-state fermentation of groundnut oil cake by Aspergillus niger: A bioprocess optimization study for animal feedstock applications - Buddhiwant, Priyanka; Bhavsar, Kavita; Kumar, V. Ravi; Khire, Jayant M. (Preparative Biochemistry & Biotechnology, 2016)
This investigation deals with the use of agro-industrial waste, namely groundnut oil cake (GOC), for phytase production by the fungi Aspergillus niger NCIM 563. Plackett-Burman design (PBD) was used to evaluate the effect of 11 process variables and studies here showed that phytase production was significantly influenced by glucose, dextrin, distilled water, and MgSO4 center dot 7H(2)O. The use of response surface methodology (RSM) by Box-Behnken design (BBD) of experiments further enhanced the production by a remarkable 36.67-fold from the original finding of 15 IU/gds (grams of dry substrate) to 550 IU/gds. This is the highest solid-state fermentation (SSF) phytase production reported when compared to other microorganisms and in fact betters the best known by a factor of 2. Experiments carried out using dried fermented koji for phosphorus and mineral release and also thermal stability have shown the phytase to be as efficient as the liquid enzyme extract. Also, the enzyme, while exhibiting optimal activity under acidic conditions, was found to have significant activity in a broad range of pH values (1.5-6.5). The studies suggest the suitability of the koji supplemented with phytase produced in an SSF process by the "generally regarded as safe" (GRAS) microorganism A. niger as a cost-effective value-added livestock feed when compared to that obtained by submerged fermentation (SmF).

Phytase production by aspergillus niger NCIM 563 for a novel application to degrade organophosphorus pesticides - Shah, Parin C.; Kumar, V. Ravi; Dastager, Syed G.; Khire, Jayant M. (AMB Express, 2017)
The production of phytase using Aspergillus niger NCIM 563 under submerged fermentation conditions was studied using protein rich chickpea flour as substrate. Employing a hybrid statistical media optimization strategy of Plackett-Burman and Box-Behnken experimental designs in shake-flasks gave an increased phytase activity from an initial 66 IU/mL in 216 h to 160 IU/mL in a reduced time of 132 h. Productivity, thus increased by 3.97 times from 7.3 to 29 IU/mL/day. Using the optimized media, the production was successfully scaled-up further and improved up to 164 IU/mL in 96 h by studies carried out employing 2 and 10-L fermenters. The enzyme supernatant was recovered using centrifugal separation of biomass and the stability of the produced phytase was tested for animal feed applications under gastric conditions. In vitro degradation studies of water soluble monocrotophos, methyl parathion and water insoluble chlorpyrifos, pesticides used extensively in agriculture was carried out. It was observed by HPLC analysis that phytase could degrade 72% of chlorpyrifos at pH 7.0, 35 degrees C. Comparable results were obtained with monocrotophos and methyl parathion. With chlorpyrifos at higher temperature 50 degrees C as much as 91% degradation could be obtained. The degradation of chlorpyrifos was further validated by spraying phytase on harvested green chilli ( Capsicum annuum L) under normal conditions of pH 7.0, 35 degrees C and the degradation products obtained analyzed by LCMS. Thus, the present study brings out a potentially novel application of phytase for biodegradation of organophosphorus pesticides.

Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region - Chakdar, Hillol; Dastager, Syed G.; Khire, Jayant M.; Rane, Digeshwar; Dharne, Mahesh S. (3 Biotech, 2018)
Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 displayed maximum mineral phosphate solubilization (1072.35mg/L) in liquid medium and during this period the pH dropped to 3.13. All five isolates had highest P solubilization at 48h after inoculation. During mineral phosphate solubilization, both gluconic acid and 2-keto gluconic acid were produced by Kosakonia and Bacillus isolates, while only 2-keto gluconic acid was detected in Pantoea isolates. Highest organic acid (39.07 +/- 0.04g/L) production was envisaged in Bacillus sp. AH9, while Pantoea sp. A34 produced the least amount (13.00 +/- 0.01g/L) of organic acid. Seed bacterization with Pantoea sp. A3 and Kosakonia sp. A37 resulted in 37% and 53% increase in root length of tomato seedlings, respectively, while Pantoea sp. A34 and Kosakonia sp. B7 had deleterious effects on root length as well as overall growth of the seedlings. To our knowledge, this is the first report of plant growth promoting potential of microorganisms isolated from termitorial soil of Sanjivani island, which is a drought-prone area. Therefore, such efficient growth promoting P solubilizers can offer an effective solution for sustainable agriculture in arid, dryland farming and drought-prone regions.

Use of Plackett-Burman design for enhanced phytase production by Williopsis saturnus NCIM 3298 for applications in animal feed and ethanol production - Pable, Anupama A.; Shah, Sarah; Kumar, V. Ravi; Khire, Jayant M. (3 Biotech, 2019)
Distiller-dried grain solid (DDGS), a co-product of alcohol production, contains cereal grain residues, proteins, and yeast metabolites, which make it suitable in poultry feeding. However, high phytate content of DDGS limits its applicability in poultry feed. In this study, Plackett-Burman design was used to improve cell-bound phytase production by Williopsis saturnus NCIM 3298, and we achieved an enzyme activity of 269IU/g of dry-wet biomass. The effect of this enhanced phytase-displaying yeast strain on hydrolysis of corn phytate and subsequently on ethanol production and DDGS quality was then investigated. Results of saccharification in the presence of phytase showed that reducing sugar content of liquefied mash increased by 11%, which subsequently improved the ethanol production by 18% (w/v) (p<0.01) compared with the control. Notably, phytase treatment decreased the phytate content of corn by 70% (p<0.01) compared with the control, thereby improving the availability of free phosphate in fermentation broth and DDGS. Thus, the results obtained suggest that the addition of W. saturnus NCIM 3298 strain has the potential of providing a new source of phytase that would be useful in the feed and ethanol industries.
Keywords: DDGS; Ethanol; Phytase; Plackett-Burman Design; Williopsis saturnus NCIM 3298

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation